Aktivitas Antijamur dari Bakteri Penghasil Senyawa Imidazole-3-Oxide terhadap Jamur Helminthosporium Maydis - Trisna Agung Phabiola; Ida Bagus Gde Pranatayana; Khamdan Khalimi (Nandur, 2024)
The fungus Helminthosporium maydis is a pathogen that causes leaf blight in corn plants.The use of biological agents is one way to control leaf blight that is environmentally friendly. One of these biological agents is bacteria that produce the compound imidazole-3-oxide. This research aims to determine the ability of bacteria producing imidazole-3-oxide compounds to inhibit the growth of H. maydis fungal colonies. The results showed that bacteria producing the compound imidazole-3-oxide were able to inhibit the growth of the fungus H. maydis in vitro with an inhibition percentage ranging from 94.74% to 95.52%. Bacterial filtrate producing imidazole-3-oxide compounds at a concentration of 20% is able to inhibit the growth of the fungus H. maydis with a percentage of inhibitory power ranging from 91.35% to 94.41% whereas at a concentration of 50% it was able to inhibit the growth of the H. maydis fungus with an inhibitory percentage of 100%. The results of this research provide new information that bacteria producing the compound imidazole-3-oxide can be used to control leaf blight disease in corn plants.